Development of an "I Love the Earth" E-Module to Support Mutual Cooperation in Early Childhood Education - Novia, Novia Sri Wilanda; Dadan Suryana; Rakimahwati; Yaswinda (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
This study examined the development and initial evaluation of an e-module themed "I Love the Earth" designed to support mutual cooperation in early childhood education. The study was motivated by the need to strengthen young children’s prosocial dispositions, particularly collaboration, caring, helping, and sharing, within the framework of the Pancasila Student Profile. It adopted a Research and Development approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The e-module was developed as a project-based digital resource that combined environmental themes with collaborative learning activities for children aged 5 to 6 years. The study involved expert validators, teachers, and children at TK Negeri Pembina Linggo Sari Baganti. The findings showed that the developed e-module obtained an average validity score of 94%, a practicality score of 93%, and an effectiveness score of 87%. Effectiveness was assessed through observational indicators related to children’s mutual cooperation during project activities, including collaboration in groups, caring for peers, empathy, helping behavior, and sharing. These results suggest that the e-module was not only feasible for classroom use, but also showed potential to support the cultivation of mutual cooperation through contextual and developmentally appropriate learning experiences. Rather than implying that digital media are inherently effective for character formation, the study indicates that digital resources may become pedagogically meaningful when they are structured around social interaction, shared activity, and children’s everyday experience. In broader terms, the study offers a contextually grounded example of how digital pedagogy, project-based learning, and value-oriented early childhood education may be brought into relation, with possible relevance for wider discussions on prosocial and environmentally situated learning in diverse educational settings.